Per un repubblicanesimo religioso. Libertà e fede nella storiografia di Maurizio Viroli (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Un’idea della politica - 2. Del rapporto costitutivo tra libertà e religione - 3. Repubblicanesimo e religione - 4. Lo spazio (pubblico) della religione.For a religious republicanism. Freedom and faith in Maurizio Viroli's historiographyABSTRACT: This article analyzes the Maurizio Viroli's historiographic thought, highlighting the central relationship between the spirit of freedom and the religious sentiment, from which a full knowledge of the public significance of religion descends.